PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdulah Rakhman; Liaw Bunfa; Hafizah Rifiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Company value is very important for shareholders to gain profits in their share peculiarities. Many fundamental factors can increase company value. This study aims to determine the effect of company size and profitability factors on firm value. This research was conducted at consumer goods companies listed on the Indonesia Stock Exchange during the 2015-2017 period. The sampling technique used was purposive sampling technique. Data analysis techniques used were data pooling test, classical assumptions test, and hypothesis test with the help of SPSS 20 and SmartPLS 3 programs. The results of this study indicate that firm size has a positive effect on firm value and profitability has a positive effect on firm value. Based on the results of the study, it can be concluded that firm size and profitability have a positive effect on the firm value of consumer goods companies. Key words: firm value, firm size, profitability